How To Start Up A Software Business Within A Cloud Computing Environment. - Buchegger, Thomas (Diplomica Verlag, 2014)
The author is beyond excited about the potential that comes from new ventures. One of the key characteristics of successful entrepreneurs is courage, but courage only is most often far too little and can end up in a fiasco soon. The author is convinced that there is a set of rules that is valid for most companies. Knowledge and usage of this set of rules could make an entrepreneurs life much easier. The key question within this book is: 'What aspects of business development are of tremendous importance for Software as a Service start up companies?' In order to find some answers to this questio.